Direct far-infrared metal abundances (FIRA): I. M101 - Lamarche, Cody; Smith, J. D.; Kreckel, Kathryn; Linden, S. T.; Rogers, N. S. J.; Skillman, E.; Berg, D.; Murphy, E.; Pogge, R.; Donnelly, G. P.; Kennicutt, R.; Bolatto, A.; et al. (The astrophysical journal, 2022)
Accurately determining gas-phase metal abundances within galaxies is critical as metals strongly affect the physics of the interstellar medium. To date, the vast majority of widely used gas-phase abundance indicators rely on emission from bright optical lines, whose emissivities are highly sensitive to the electron temperature. Alternatively, direct-abundance methods exist that measure the temperature of the emitting gas directly, though these methods usually require challenging observations of highly excited auroral lines. Low-lying far-infrared (FIR) fine structure lines are largely insensitive to electron temperature and thus provide an attractive alternative to optically derived abundances. Here, we introduce the far-infrared abundance (FIRA) project, which employs these FIR transitions, together with both radio free-free emission and hydrogen recombination lines, to derive direct, absolute gas-phase oxygen abundances. Our first target is M101, a nearby spiral galaxy with a relatively steep abundance gradient. Our results are consistent with the O++ electron temperatures and absolute oxygen abundances derived using optical direct-abundance methods by the CHemical Abundance Of Spirals (CHAOS) program, with a small difference (∼1.5σ) in the radial abundance gradients derived by the FIR/free-free-normalized versus CHAOS/direct-abundance techniques. This initial result demonstrates the validity of the FIRA methodology—with the promise of determining absolute metal abundances within dusty star-forming galaxies, both locally and at high redshift.
Gesehen am 20.04.2022